Metal-organic framework single crystal for in-memory neuromorphic computing with a light control - Semyon V. Bachinin; Alexandr Marunchenko; Ivan Matchenya; Nikolai Zhestkij; Vladimir Shirobokov; Ekaterina Gunina; Alexander Novikov; Maria Timofeeva; Svyatoslav A. Povarov; Fengting Li; Valentin A. Milichko (Communications Materials, 2024)
Abstract Neuromorphic architectures, expanding the limits of computing from conventional data processing and storage to advanced cognition, learning, and in-memory computing, impose restrictions on materials that should operate fast, energy efficiently, and highly endurant. Here we report on in-memory computing architecture based on metal-organic framework (MOF) single crystal with a light control. We demonstrate that the MOF with inherent memristive behavior (for data storage) changes nonlinearly its electric response when irradiated by light. This leads to three and more electronic states (spikes) with 81 ms duration and 1 s refractory time, allowing to implement 40 bits s−1 optoelectronic data processing. Next, the architecture is switched to the neuromorphic state upon the action of a set of laser pulses, providing the text recognition over 50 times with app. 100% accuracy. Thereby, simultaneous data storage, processing, and neuromorphic computing on MOF, driven by light, pave the way for multifunctional in-memory computing architectures.